QARAQALPAQ XALÍQ DÁSTANLARÍNDA TUWÍSQANLÍQ ATAMALARDAǴÍ GENDERLIK ÓZGESHELIKLER - Rzamuratova, Z. (SCIENCE and SOCIETY, 2024)
In this article, genderlects and their characteristics, which are of special importance in gender linguistics, are studied. Fertility terms distinguished by gender characteristics, their types applied to women and men are analyzed. Also, there are examples of the types of masculinity and feminism used in reference to girls, women, brides or boys, men.
Keywords: gender stereotype; genderlect; sociolect; feminist; masculinism; etymology; phraseologism